Decidualization of Stromal Cells Promotes Involvement of Mast Cells in Successful Human Pregnancy by Increasing Stem Cell Factor Expression - Ueshima, Chiyuki; Kataoka, Tatsuki R.; Osakabe, Mitsumasa; Sugimoto, Akihiko; Ushirokawa, Akihiko; Shibata, Yuji; Nakamura, Hiroya; Shibuya, Rintaro; Minamiguchi, Sachiko; Sugai, Tamotsu; Haga, Hironori (Frontiers in Immunology, 2022)
Decidualization of endometrial stromal cells and the presence of immunocompetent cells, including human mast cells, play important roles in the establishment of pregnancy. In the present study, the effects of decidualization of endometrial stromal cells on the function of decidual mast cells were elucidated. The in vitro assay revealed that decidualization of an endometrial stromal cell line, T HESCs, increased stem cell factor (SCF) mRNA expression. Decidualization of T HESCs enhanced the production of leukemia inhibitory factor (LIF), and the migration of LAD2 cells when co-cultured with T HESCs and LAD2 cells. In addition, decidualization of T HESCs enhanced cell migration in a human trophoblast cell line, HTR-8/SVneo, increased CD9 expression, a marker for extravillous trophoblast (EVT) differentiation, and decreased the secretion of  human chorionic gonadotropin (hCG), a marker for syncytiotrophoblast (ST) differentiation, when co-cultured with T HESCs, LAD2 cells, and HTR-8/SVneo cells, in a LIF-dependent manner. Pathological samples from uterine pregnancies, including decidual stromal cells, showed increased SCF mRNA expression, mast cell numbers and LIF mRNA expression thereof compared with tubal pregnancy. SCF produced by decidual stromal cells enhanced the migration and LIF production of mast cells, and promoted the migration and differentiation of trophoblasts to increase the likelihood of successful human pregnancy.